The impact of iron impurities on Al-2.24Mg-2.09Li alloy microstructure changes during compression testing - Kozina, Franjo; Zovko Brodarac, Zdenka; Petrič, Mitja; Penko, Andrej (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
As a major impurity element in aluminium-lithium alloys, iron (Fe) reduces formability, fracture toughness and fatigue resistance by solidifying as Al6Fe and Al3Fe phases. This research was performed in order to estimate the impact of Fe impurities on Al-2.24Mg-2.09Li alloy microstructure changes in as cast and solution hardened condition during compression testing. The solution hardening was applied in order to improve mechanical properties by dissolving intermetallic particles and bulking αAl matrix with Mg. However, the higher yield strength at 0.2% deformation, compression strength and temperature increase during testing were determined in as cast condition. The focus of this investigation was to establish the influence of Fe phases on obtained differences in properties. Microstructural investigation revealed significant differences in microstructure change during compression testing of as cast and solution hardened samples. Although the barrelling effect led to the unequal deformation and surface texture development, the eutectic Al3Fe particles positioned in the αAl interdendritic areas did not significantly impact microstructure changes of as cast sample during compression. Even due the solution hardening led to bulking of αAl matrix with Mg and Fe, the Al3Fe particles were not dissolved. The coarse morphology of Al3Fe particles and theirs position at the grain boundaries of αAl grain contributed to low energy intergranular fracture nucleation and progress across the grain boundaries resulting in lower strength value.
Keywords: Al-Mg-Li alloy; Iron impurities; Solution hardening; Compression testing; Microstructure; Low energy intergranular fracture